Implementación de un plan de mejora continua en el área de Producción de una empresa láctea. - Bermúdez Vera, Luiggi Alexander (2020)
The research focused on the implementation of a continuous improvement plan through visual management in a dairy company, the main objective was to launch a key tool for continuous improvement, the 5’S to generate greater productivity and a better work environment which help to foster a culture of quality in employees. The methodology to form two working groups, which are in contact with each area of the Production Department, with the intention of identifying, feeling the need for change, and managing the resources needed to obtain positive results of the implementation. For this, they were trained with the intention that they can understand what this plan is and allow the company to carry out excellence. The first group was in charge of guiding the implementation process implemented with the second group in the audits and the execution of the improvement that was made in each area. The first audit with the working group was carried out with the determination of having an initial diagnosis of the place where it is implemented, identifying the necessary of the unnecessary, verifying if each object had a specific place, the sources of dirt were identified and it was checked if there is compliance with order, cleanliness, classification, to generate a standard and have a good discipline. This got to know everything that is needed for the implementation and a planning was made of it. The execution or implementation was the fundamental part since here the administrative and operational personnel participated in the change that the Production Department needed, where the chiefs helped in each area and the operators collaborated in the location and delimitation of what was really necessary, once this event is completed, a photographic and comparative survey about before and after of the area state. Finally, a daily audit was carried out for 21 days in order to verify that the changes made are maintained, what is known about the status of each area and demonstrate a "Gestores del Cambio" blackboard, as a tool for visual management, thus generating discipline in the personnel, diverse audits allowed to identify the opportunities of continuous improvement.